β-hydroxybutyrate enhances bovine neutrophil adhesion by inhibiting autophagy - He, Jiyuan; Wang, Kexin; Liu, Mingchao; Zeng, Wen; Li, Dong; Majigsuren, Zolzaya; Batbaatar, Tugsjargal; Li, Yunfei; Liu, Siyuan; Du, Xiliang; Lei, Lin; Song, Yuxiang; et al. (Frontiers in Immunology, 2023)
Subclinical ketosis (SCK) in dairy cows, a common metabolic disorder during the perinatal period, is accompanied by systemic inflammation and a high concentration of blood β-hydroxybutyrate (BHB). BHB induced adhesion of neutrophils may play a crucial role in the development of systemic inflammation in SCK cows. Autophagy, an intracellular degradation system, regulates the recycling of membrane adhesion molecules and may be involved in BHB regulating adhesion and pro-inflammatory activation of bovine neutrophils. Thus, the objective of this study was to determine the relationship between BHB, autophagy, and neutrophil adhesion. Here, elevated abundance of serum amyloid A, haptoglobin, C-reactive protein, interleukin-1β, interleukin-6, and tumor necrosis factor-α were found in SCK cows, and all these pro-inflammatory factors had a strong positive correlation with serum BHB. After BHB treatment, the number of adherent neutrophils and the adhesion associated protein abundance of both total and membrane CD11a, CD11b, and CD18 was greater, confirming that BHB promoted the adhesion of bovine neutrophils. However, the mRNA abundance of ITGAL (CD11a), ITGAM (CD11b), and ITGB2 (CD18) did not show a significant difference, suggesting that the degradation of adhesion molecules may be impaired. Transmission electron microscopy revealed a decreased number of autophagosomes and a decrease in mRNA abundance of SQSTM1 (p62) and MAP1LC3B (LC3) after BHB treatment. In parallel, protein abundance of p62 increased while the ratio of protein LC3 II to LC3 I decreased after BHB treatment, indicating that BHB inhibits autophagy of bovine neutrophils. To confirm the regulatory role of autophagy in BHB promoting neutrophil adhesion, we used an autophagy activator rapamycin (RAPA). Data showed that RAPA relieved the inhibitory effect on autophagy and the promotive effect on cell adhesion induced by BHB. Importantly, BHB inhibited the colocalization of LC3 and CD11b, which was relieved by RAPA, further confirming the regulatory role of autophagy in the recycling of the above adhesion molecules. Furthermore, BHB treatment increased the mRNA abundance and the release of pro-inflammatory factors IL-1B, IL-6, and TNF of bovine neutrophils, and these effects were attenuated by RAPA. Overall, the present study revealed that BHB promotes the adhesion of bovine neutrophils by inhibiting autophagy.